Efektifitas dan Efisiensi Penyelesaian Sengketa Ekonomi Syariah di Peradilan Agama - Hasanuddin Muhammad (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2020)
The Supreme Court, as the highest judicial body, should ensure the realization of effective and efficient justice with the principles of simplicity, speed, and affordability. This study assesses the extent to which Supreme Court Regulations govern and achieve an effective and efficient judicial system in resolving Islamic economic disputes within religious courts. Employing a qualitative approach with a normative juridical perspective, it was found that the Supreme Court has enacted various regulations to enhance the efficiency of the judiciary. These include Supreme Court Regulation Number 2 of 2015 on the procedure for simple lawsuit resolution, Supreme Court Regulation Number 14 of 2016 on Procedures for Settling Sharia Economic Disputes, Regulation of the Supreme Court Number 5 of 2016 concerning Sharia Economic Judge Certification, Supreme Court Regulation 04 of 2019 amending Supreme Court Regulation Number 02 of 2015 on Simple Settlement Procedures, and Supreme Court Regulation 01 of 2019 on Electronic Case and Trial Administration. These regulations aim to streamline the resolution of Sharia economic disputes by facilitating simple lawsuit procedures, ensuring the competence of judges in Sharia economics through certification, and implementing electronic judicial services.